#MeToo, white feminism and taking everyday politics seriously in the global political economy. Issue 4 (2nd October 2019) - Griffin, Penny
ABSTRACT: This paper examines social media movements, specifically #MeToo, in relation to the politics of feminism and white privilege in the contemporary global political economy. Analysis of social media movements is located as a key part of the intricate web of practices that enable certain types of gendered identity and socioeconomic privilege to intersect, in powerful ways and to potent effect. The paper argues that, while scholarship on the global political economy has not often taken seriously popular culture sources in and across world politics, and needs to do better in this regard, investigating the politics of popular culture, race and socioeconomic privilege in contemporary world politics is important. This is because such analysis foregrounds everyday, cultural practices of knowledge formation, building space for emphasising relations of power but also highlighting the possibilities of and for resistance, agency and avenues for creative thinking and doing in world politics.